2020
DOI: 10.1038/s41386-020-0718-8
|View full text |Cite
|
Sign up to set email alerts
|

Me, myself, bye: regional alterations in glutamate and the experience of ego dissolution with psilocybin

Abstract: There is growing interest in the therapeutic utility of psychedelic substances, like psilocybin, for disorders characterized by distortions of the self-experience, like depression. Accumulating preclinical evidence emphasizes the role of the glutamate system in the acute action of the drug on brain and behavior; however this has never been tested in humans. Following a double-blind, placebo-controlled, parallel group design, we utilized an ultra-high field multimodal brain imaging approach and demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 104 publications
12
143
1
1
Order By: Relevance
“…In turn, enhancing natural reward via mindfulness practice is theorized to restructure reward processing by shifting valuation of drug-related rewards back to valuation of natural rewards, and thereby reducing addictive behavior [53]-a contention supported by recent neurophysiological data in chronic opioid users [31]. This possibility is especially intriguing, given the role of glutamatergic mPFC activity in both ego dissolution occasioned by psychedelics [54], reward, and the regulation of chronic opioid use [4]. Thus, Veterans who learned to self-generate internal reward via meditation may have been less compelled to consume opioids to obtain hedonic equilibrium, which may have accounted for the observed opioid sparing effects of MORE.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, enhancing natural reward via mindfulness practice is theorized to restructure reward processing by shifting valuation of drug-related rewards back to valuation of natural rewards, and thereby reducing addictive behavior [53]-a contention supported by recent neurophysiological data in chronic opioid users [31]. This possibility is especially intriguing, given the role of glutamatergic mPFC activity in both ego dissolution occasioned by psychedelics [54], reward, and the regulation of chronic opioid use [4]. Thus, Veterans who learned to self-generate internal reward via meditation may have been less compelled to consume opioids to obtain hedonic equilibrium, which may have accounted for the observed opioid sparing effects of MORE.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most robust effects of salvinorin A was a decrease in sFC within the DMN, and using connectomebased classification, we found within-DMN sFC and eFC to be especially predictive of the effects of SA on brain function compared to other network interactions. Decreases in DMN sFC during the acute effects of hallucinogens have been a replicable finding, occurring with psilocybin 30,34 , LSD 25,35 , DMT 33 , and ketamine 31,32 . Although it might be tempting to speculate that these effects reflect "ego dissolution" 30,40 , decreases in sFC within the DMN have also been observed with acute administration of drugs not typically associated with ego dissolution such as THC 62 , alcohol 63 , and amphetamine 64 .…”
Section: Discussionmentioning
confidence: 95%
“…Like classic psychedelics 25 27 and dissociative anesthetics 28 , 29 , SA decreased oscillatory power in low frequency bands at rest, suggesting that pharmacologically distinct hallucinogens have partially overlapping neural mechanisms. In functional magnetic resonance imaging (fMRI) studies, both classic psychedelics and dissociative anesthetics have been shown to decrease static functional connectivity (sFC; the strength of association between brain regions over time) within canonical resting state networks, especially within the default mode network (DMN) 25 , 30 35 , increase between-network sFC 25 , 31 , 35 37 , and increase or decrease sFC among visual regions 25 , 34 , 35 , 38 , 39 . A recent hypothesis suggests that classic psychedelics make the brain more “entropic,” particularly among interactions involving the DMN 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…This is noteworthy because DMN disintegration has been reported when scanning participants during the psychedelic experience (Carhart-Harris et al, 2012;Preller et al, 2020) and may be implicated in the therapeutic effects of psilocybin as DMN connectivity is elevated in a range of conditions and is reduced following administration of psilocybin to experienced meditators (Smigielski et al, 2019;Whitfield-Gabrieli and Ford, 2012). Although we do not see a persistent effect on DMN connectivity, acute disruption of the DMN may still be therapeutically relevant (Carhart-Harris and Friston, 2019;Mason et al, 2020). Intake of both Salvinorin-A, a 5-HT2AR-independent hallucinogen, and MDMA, which has a subjective effect profile distinct from serotonergic psychedelics (Doss et al, 2020;Müller et al, 2020;Roseman et al, 2014), leads to a reduction in DMN connectivity.…”
Section: Additional Effects On Connectivitymentioning
confidence: 51%